Socio-economic factors of students' academic performance (using the example of a sociological study of Barnaul) - Akhmedova, Angelina Rustamovna; Chukanova, Tat'yana Viktorovna; Vasilenko, Irina Aleksandrovna; Mazailova, Tatyana Aleksandrovna (Социодинамика, 2025)
The subject of this research is the socio-economic factors of students' academic performance. By socio-economic factors, the author means those factors in which people's lives are influenced by their economic status, origin and occupation. The author examines the main determinants affecting the educational activities of students. The author analyzes in detail the relationship between the financial situation of a student's family and his academic results. Such indicators as income level, housing conditions, availability of educational resources and the possibility of additional training are considered. Statistically significant correlations between these indicators and students' academic performance are revealed. The influence of education and professional employment of parents, their social circle and the degree of involvement in the educational process is investigated. It analyzes how social connections and family resources contribute to or hinder academic success. The sample used for the survey consists of students of higher educational institutions in Barnaul. The sample is based on a cluster selection system for respondents. The sample population of the study consisted of 228 respondents. The author came to the conclusion that among the main factors affecting academic performance, one can single out the financial situation of students' families, housing conditions, job availability, motivation to study, and others. These factors must be taken into account when developing educational programs and strategies for the development of educational institutions. Further research in this area may be aimed at a deeper study of the identified factors, as well as at expanding the sample to include other regions. This will provide a more complete picture of the impact of socio-economic factors on students' academic performance and develop more effective measures to improve the quality of education. The author also emphasizes the need to develop and implement effective social programs aimed at creating equal educational opportunities for all students, regardless of their socio-economic background.